Phraseologische Strukturen in Hermann Kinders autobiografischer Krankheitserzählung „Der Weg allen Fleisches“ (2014) - Thienel, Christian (Kalbotyra, 2020)
Hermann Kinder’s novel contains a conspicuous number of phraseological elements, which is unusual for the writing style of this author. The article describes the accumulation of phraseological and idiomatic material and its usage as a literary stylistic resource. The analysis focuses on the relation of the linguistic appearance and the aesthetic function of the phraseologisms. Therefore, the article intends to contribute to an interdisciplinary method of interpretation, linking linguistic and literary studies. It also includes psychoanalytic concepts to describe the author’s specific linguistic expression of his autobiographical experience of illness. The aesthetic function of the phraseologisms and idiomatic phrases changes in relation to the novel’s progress. In the beginning, collocations increase the cohesion of the text in order to create an image of health. When the disease becomes more and more evident, the emotional affection of the protagonist is being controlled by formulistic linguistic elements. In addition, the author unmasks the pragmatic automatism of the medical language and the failure of its empathetic function by ironically evoking the ambiguity of idiomatic phrases. As a contrast, the narrator refers back to a comforting symbolic language by using linguistic patterns of fairy tales as an imitation of phraseological components. As a result, the analysis indicates that the inclusion of phraseological material in this literary pathobiography seems to provide a linguistic space of shelter for the suffering protagonist. The context-related, varying usage of phraseologisms in this text also seems to linguistically reflect a collective, culturally overarching psychosomatic experience of illness.